Enhancement of superconducting properties in polycrystalline Fe(Se, Te) via a dual coordination effect. (August 2019) - Liu, Jixing; Zhang, Shengnan; Sang, Lina; Li, Meng; Zhao, Weiyao; Li, Zhi; Cheng, Zhenxiang; Liu, Liqiang; Feng, Jianqing; Li, Chengshan; Zhang, Pingxiang; Dou, Shixue; et al.
Abstract: Cl-doped Fe(Se, Te) superconductors were fabricated through a melting method followed by hydrostatic pressure (HP) post treatment. A dual coordination effect has been aroused, viz. the introduction of Cl − ions triggered the nucleation and growth of nanometric point-like secondary phase as extra pinning centers, while HP strengthened the pinning competence of these point defects. As a result, the superconducting phase volume, critical temperature, and critical current density have been improved by 12.2%, 42.3%, and nearly 100 times, respectively, compared with the undoped sample without HP. Graphical abstract: Unlabelled Image